2005
DOI: 10.1159/000083978
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibody to Hepatitis E Virus among Haemodialysis Patients in Taiwan: Possible Infection by Blood Transfusion

Abstract: Background/Aims: A higher prevalence of anti-hepatitis E virus (HEV) in non-endemic viral hepatitis such as in Germany has been reported in our previous study. The aim of this study was to assess the seroepidemiology of HEV among haemodialysis (HD) patients in Shin-Kong Hospital, Taiwan, and to evaluate whether there was an increased risk of infection and exposure to HEV even in an area of endemic viral hepatitis. Methods: Serum samples obtained from 400 Taiwanese patients on chronic HD (group 1), 400 sex- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Three cases were immunocompromised due to malignant disease and one due to usage of immunosuppressive drugs. Two of the cases with malignancies had received multiple blood transfusions during the estimated incubation period which might be the source of their infection, as transmission of HEV via blood has previously been described [32-34]. Trace back of donor blood for these two cases was, however, not considered at the time of this investigation because a relationship with blood donation was thought to be unlikely by the treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…Three cases were immunocompromised due to malignant disease and one due to usage of immunosuppressive drugs. Two of the cases with malignancies had received multiple blood transfusions during the estimated incubation period which might be the source of their infection, as transmission of HEV via blood has previously been described [32-34]. Trace back of donor blood for these two cases was, however, not considered at the time of this investigation because a relationship with blood donation was thought to be unlikely by the treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…Such a possibility was supported by the observation that anti-HEV antibody was more frequent in transfusion recipients than in non-transfused controls [33] . Several studies concerning HEV epidemiology among chronic hemodialysis patients have been performed [10,30,[34][35][36][37][38] . Except Fabrizi et al [30] , all these studies indicated significantly higher risks of HEV infection in chronic hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is certainly wise to take precautions in highly endemic areas to reduce the risk of HEV infection among HD patients. So far, there have been reports of separate trends in HD units in contrast to the general population [58,59]. As a result, although significant transmission of HEV may occur from sporadic cases or an outbreak in the community to HD centers, risk factors and epidemiological trends might be quite different.…”
Section: Epidemiological Considerations For Hev Transmission In Hd Cementioning
confidence: 99%